The United Nations and nuclear orders - Boulden, Jane, 1962-; Thakur, Ramesh Chandra, 1948-; Weiss, Thomas George (United Nations University Press, 2009)
This book examines actors, tools, and issues associated with the changing nature of the environment in which the United Nations operates; the ways in which it has responded and might respond to technological and political problems; and the questions and difficulties that arise for the world organization. Issues covered in the book include doctrinal questions on the use of force, the regional dynamics of nuclear proliferation, and the growing concern that nuclear order established by the NPT may collapse or simply be overtaken by events.--Publisher's description.